Biohybrid Nanostructures: Gap Plasmon of Virus‐Templated Biohybrid Nanostructures Uplifting the Performance of Organic Optoelectronic Devices (Advanced Optical Materials 11/2020). Issue 11 (5th June 2020) - Lee, Hock Beng; Kim, Won‐Geun; Lee, Miso; Lee, Jong‐Min; He, Siwei; Kumar, Neetesh; Devaraj, Vasanthan; Choi, Eun Jung; Jeon, Il; Song, Myungkwan; Oh, Jin‐Woo; Kang, Jae‐Wook
Abstract : As demonstrated by Jin‐Woo Oh, Jae‐Wook Kang and co‐workers in article number 1902080, the M13 bacteriophage can be used as a biological scaffold for the controlled densification of silver and gold nanoparticles, yielding a novel biohybrid nanostructure with fascinating gap‐plasmon effect. The binder‐free, charge driven synthesis mechanism of the nanostructures is presented. The resulting phage nanostructural network is successfully applied as a bifunctional optical enhancer–interfacial layer in organic solar cells and organic light‐emitting diodes.